Evaluation of the use of Agrohomeopathy and Trichoderma sp. in the productivity of rice susceptible to blast (Research, Society and Development, 2020)
The use of chemical inputs in agriculture has grown significantly in recent years, making agricultural practice unsustainable. Although pesticides have facilitated the rapid control of pests and diseases, in the long term the degree of imbalance and disintegration of the biota increased, making it interesting to use alternative methods of management. The objective of this work was to evaluate the final productivity of the cultivar Guri INTA CL, susceptible to blast, submitted to different treatments based on the use of conventional chemical product (C), homeopathy (H), homeopathy and Trichoderma sp (H + B) and control without treatment (T). The experiment was carried out at the IRGA (Rio Grandense do Arroz Institute) in Cachoeira do Sul in the 2018/19 harvest, verifying productivity through the final grain weight obtained after the harvest of five sample plots 4.8 m2 per treatment. The H+B treatment showed the highest average productivity, 9,711 kg ha-1, which corresponds to an 8% increase in productivity compared to the control, followed by H>T>C. The results indicate the potential of combining homeopathy and Trichoderma in reducing the use of chemical inputs in rice fields.